Utilization of Interactive Media Articulate Storyline In Chemical Bonding Learning For Grade X High School - Yaparno Famahato Daeli; Pasar Maulim Silitonga (Universitas Negeri Medan, 2023)
Educational media can enhance student outcomes and interest in learning about chemical bonds. This study utilized an interactive learning media, Articulate Storyline. This research attempts to: 1) Determine the learning outcomes of students taught using Articulate Storyline and 2) their interest in learning compared to conventional educational media, namely PowerPoint; and 3) identify the correlation between learning outcomes and the interest of students taught with Articulate Storyline. 50 students from classes X-3 and X-9 were selected based on their homogeneity status as the sample. A two-tailed t-test and a correlation coefficient test data analysis. Results: 1) The learning outcomes of students using Articulate Storyline were higher than those using PowerPoint, with scores obtained by students using Articulate Storyline (86.4 ± 4.90) and PowerPoint (81.4 ± 6.54), and a tcount (3.059) > ttable (1.677). 2) The learning interest of students using Articulate Storyline was higher than that of students using PowerPoint, with scores obtained by students using Articulate Storyline (82.65 ± 2.22) and PowerPoint (79.70 ± 2.85), and a tcount (3.94) > ttable (1.677). 3) There was a positive correlation between the learning outcomes and interest of students taught with Articulate Storyline, where the calculated rcount (0.931) > rtable (0.396).